TMS and EEG Pharmacodynamic Effects of a Selective Sphingosine‐1‐Phosphate Subtype 1 Receptor Agonist on Cortical Excitability in Healthy Subjects - Cuba, Catherine M. K. E.; Goede, Annika A.; Klaassen, Erica S.; Otto, Marije E.; Doll, Robert J.; Kim, Jessica; Demitrack, Mark A.; Chen, Ruihua; Groeneveld, Geert Jan; Heuberger, Jules A. A. C. (Clinical pharmacology and therapeutics, 2025)
Current anti‐epileptic drugs lack efficacy, cause many side effects and one third of all patients are treatment‐resistant. Drugs targeting the sphingosine‐1‐phosphate receptor show potential anti‐convulsant effects in animal models and decrease cortical excitability in patients with multiple sclerosis, but available compounds alter lymphocyte trafficking and cause immunosuppression, limiting their clinical anti‐epileptic potential. TRV045 is a selective sphingosine‐1‐phosphate subtype 1 receptor agonist without effects on lymphocyte trafficking, demonstrating efficacy in animal models of epilepsy, with the potential to target abnormal cortical excitability. This randomized, double‐blind, placebo‐controlled, two‐way cross‐over, multiple‐dose study evaluated the effects of TRV045 on cortical excitability in healthy male adults, measured by pharmaco‐electroencephalography and transcranial magnetic stimulation (TMS). Subjects received TRV045 250 mg or placebo, once daily for 4 days, in randomized order. Endpoints were analyzed with a mixed effects model analysis of covariance. Twenty‐five of the 27 subjects completed the study. There was a significant increase in alpha power with eyes open after treatment with TRV045 on Day 1, increasing after 4 days of dosing. Less pronounced significant effects in beta, gamma, and delta power were observed after 4 days. For TMS‐Electromyography there was a non‐significant decreased post‐dose single‐pulse peak‐to‐peak amplitude on Day 1 only, and there were no effects on paired‐pulse parameters. Several significant TMS‐Electroencephalography clusters were seen after 4 days of dosing. These findings show that TRV045 has central nervous system activity with evolving effects following repeated dosing. These data support further studies to elucidate the mechanism of action of TRV045 and its potential anti‐epileptic effects.